Theory of phase-adaptive parametric cooling - Ghosh, Alekhya; Kumar, Pardeep; Sommer, Christian; Jimenez, Fidel G.; Sudhir, Vivishek; Genes, Claudiu (Physical Review A, 2023)
We propose an adaptive phase technique for the parametric cooling of mechanical oscillators. Our scheme calls for a sequence of periodic adjustments of the phase of a parametric modulation of the mechanical oscillator that is conditioned on measurements of its two quadratures. The technique indicates an exponential loss of thermal energy at initial high occupancies, similar in performance to other optomechanical techniques such as cold-damping or cavity self-cooling. As the quantum ground state is approached, the phase adaptive scheme leads to residual occupancies at the level of a few phonons owing to the competition between parametric amplification of quantum fluctuations and the feedback action.
CRIS-Team Scopus Importer:2023-06-30